Cognitive technologies - Paradisi, Alberto; Mello, Alan Godoy Souza; Figueiredo, Fabrício Lira; Figueiredo, Rafael Carvalho (Springer, 2017)
This book focuses on the next generation optical networks as well as mobile communication technologies. The reader will find chapters on Cognitive Optical Network, 5G Cognitive Wireless, LTE, Data Analysis and Natural Language Processing. It also presents a comprehensive view of the enhancements and requirements foreseen for Machine Type Communication. Moreover, some data analysis techniques and Brazilian Portuguese natural language processing technologies are also described here.
Keywords: Cognitive radio networks.; elektronické knihy; electronic books